Factores de riesgo para cáncer cervicouterino en la población del HGZ/MF No.12 de enero a diciembre de 2020 - Pérez Esteban, Alfredo (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Introduction. Cervical cancer is the second leading cause of mortality due to gynecological neoplasms. HPV infection, sexually transmitted infections, parity and smoking have been associated to a variable degree to the appearance of cervical cancer. Objectives: To determine the risk factors for cervical cancer in patients of HGZ/MF No. 12 from January to December 2020. Material and methods: An observational, descriptive, retrospective study was carried out from January to December 2020. Thirty patients with a diagnosis of CaCu were studied and risk factors were obtained. Descriptive statistics, standard deviation and variable association were applied. SIRELCIS registry R-2022-1603-002. Results: The mean age was 46.97 + 15.48 years, with onset of active sexual life between 16.83 + 1.74 years; the frequency of pap smears was every 1.76 + 0.93 years; with a higher prevalence of single-partner patients 1 + 0.547. Eighty percent of the women had some type of sexually transmitted infection, while HPV was present in 40% of the patients. Smoking was present in 2% of the population. Conclusions: Sexually transmitted infections represented a high percentage for risk of CaCu, having a high number of sexual partners is also considered an associated factor, however, in this study it was shown that it is not an absolute condition. Smoking and other conditions are factors with a lower percentage of association.

Introducción. El cáncer cervicouterino representa la segunda causa de mortalidad por neoplasias ginecológicas. La infección por VPH, infecciones de transmisión sexual, paridad y tabaquismo, se han asociado en grado variable a la aparición del mismo. Objetivos: Determinar los factores de riesgo para cáncer cervicouterino en pacientes del HGZ/MF No. 12 de enero a diciembre del 2020. Material y métodos: Se realizó un estudio observacional, descriptivo, retrospectivo de enero a diciembre de 2020. Se estudiaron 30 pacientes con diagnóstico de CaCu de quienes se obtuvieron los factores de riesgo. Se aplicó estadística descriptiva, desviación estándar y asociación de variables. Registro SIRELCIS R-2022-1603-002. Resultados: La edad promedio fue 46.97 + 15.48 años, con inicio de vida sexual activa entre los 16.83 + 1.74 años; la frecuencia de papanicolau fue cada 1.76 + 0.93 años; con mayor prevalencia de pacientes de una sola pareja 1 + 0.547. El 80% de las mujeres presento algún tipo infección de transmisión sexual, mientras que el VPH, se mostró en el 40% de las pacientes. El tabaquismo se presentó en el 2 % de la población. Conclusiones: Las infecciones de transmisión sexual representaron un porcentaje alto para riesgo de CaCu, tener un número elevado de parejas sexuales también es considerado un factor asociado, sin embargo, en este estudio se demostró que no es una condición absoluta. El tabaquismo y otras condiciones, son factores con un porcentaje de menor asociación.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2024-0091; Factores de riesgo; Cáncer cervicouterino; Virus del papiloma humano; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18726